2008
DOI: 10.1111/j.1745-7254.2008.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of human fetal smooth muscle cells from arterial duct to retinoid acid

Abstract: Aim: The aim of the present study was to understand the role of retinoic acid (RA) in the development of isolated patent ductus arteriosus and the features of arterial duct-derived vascular smooth muscle cells (VSMC). Methods: The VSMC were isolated, and the biological characteristics and the response to RA were investigated in the arterial duct, aorta, and pulmonary artery VSMC from 6 human embryonic samples. Western blotting, immunostaining, and cell-based ELISA were employed to analyze the proliferation reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Importantly, such activation was absent in adjacent aortic or pulmonary arterial segments (18). Similarly, several other studies support the role of RAR in DA closure (1921). However, further investigation is needed to determine the therapeutic potential of these pathways for treating PDA.…”
Section: Discussionsupporting
confidence: 65%
“…Importantly, such activation was absent in adjacent aortic or pulmonary arterial segments (18). Similarly, several other studies support the role of RAR in DA closure (1921). However, further investigation is needed to determine the therapeutic potential of these pathways for treating PDA.…”
Section: Discussionsupporting
confidence: 65%
“…Retinoic acid also participates in vascular remodeling via promoting SMC and ECM proliferation. Wu et al showed that retinoic acid stimulated the growth of DASMCs by the stimulation of proliferating cell nuclear antigen expression and decreased apoptosis [ 54 ]. Yokoyama et al demonstrated that maternally administrated vitamin A increased the production of fibronectin and hyaluronic acid, promoting intimal thickening in the DA at preterm rats [ 55 ].…”
Section: Anatomical Closurementioning
confidence: 99%
“…Retinoic acid stimulates the growth of SMCs and decreases apoptosis ( 86 ). Prenatal administration of vitamin A increases the production of fibronectin and hyaluronic acid, leading to intimal tickening, as well as the intracellular calcium response and the contractile response of the ductus to oxygen ( 50 ).…”
Section: Anatomic Closure and Remodelingmentioning
confidence: 99%